Revitalización y articulación del espacio urbano residual como estrategia de conexión entre zona oeste de la ciudad y cerro Tres Cruces en Santiago de Cali, Valle del Cauca (2024)
The present research work is located in the city of Santiago de Cali, in the western area of the city. Having as a general objective a sustainable urban design proposal for the revitalization of residual spaces in the infrastructure of public space in the place under study.